Predictors of 2-Year PROMIS Physical Function After Primary ACL Reconstruction - Jain, Sara; McCurdy, Michael A.; Henry, Leah E.; Ventimiglia, Dominic J.; Meredith, Sean J.; Packer, Jonathan D.; Henn III, R. Frank; Leong, Natalie L. (The Journal of Knee Surgery, 2025)
The Patient-Reported Outcomes Measurement Information System (PROMIS) is a common patient-reported outcome (PRO) instrument used to evaluate function, pain, satisfaction, and mental health outcomes after surgery. Predictors of 2-year PROMIS physical function (PF) after knee surgery have been previously reported; however, PROMIS PF 2 years after anterior cruciate ligament reconstruction (ACLR) has not been well studied. The aim of this study was to investigate associations and identify predictors of 2-year PROMIS PF after primary ACLR. A prospectively managed orthopaedic registry was queried for patients who underwent primary ACLR between 2015 and 2018. PROs were collected at baseline and 2 years postoperatively, along with self-reported socioeconomic and demographic information. Bivariate analysis was performed to identify associations between baseline characteristics and 2-year PROMIS PF. Multivariate regression analysis was performed to identify predictors of 2-year and 2-year improvement in PROMIS PF. Of 203 eligible patients, 141 patients (70%) completed 2-year surveys and were analyzed. Better 2-year PROMIS PF was associated with student status (p = 0.007), younger age (p = 0.026), lower body mass index (p < 0.001), and lower Charlson Comorbidity Index (p = 0.023). Greater improvement in PROMIS PF at 2 years was associated with private insurance (p = 0.029) and income over $70,000 (p = 0.007). Better baseline PROs were associated with better 2-year PROMIS PF. Younger age (p = 0.003), higher income (p = 0.023), and better baseline PROMIS Fatigue (p < 0.001) were significant predictors of better 2-year PROMIS PF. Additionally, younger age (p = 0.003), higher income (p = 0.029), worse baseline PROMIS PF (p < 0.001), and better baseline PROMIS Fatigue (p < 0.001) were significant predictors of greater 2-year improvement in PROMIS PF. Age, income, and baseline PROMIS Fatigue independently predicted 2-year PROMIS PF and improvement in 2-year PROMIS PF. Though these factors are nonmodifiable, these findings may allow surgeons to more effectively counsel patients preoperatively.
Keywords: patient-reported outcomes; PROMIS; ACL reconstruction; physical function; predictors